Do Gig Workers Prefer Money to Flexibility? Insights from a Discrete-Choice Experiment in Malaysia - Yashodhan Ghorpade; Alyssa Jasmin; Amanina Abdur Rahman (Institute of Labor Economics (IZA), 2024)
The changing nature of work, accelerated by the experience of the COVID-19 pandemic has resulted in several fundamental shifts in the terms and conditions of work. Overlain with a clear trend of increased non-standard employment, including through the gig economy and platform work, this poses critical questions for policies and practices of the organization of work arrangements, and about who may bear the costs of emerging arrangements. We attempt to understand whether workers in freelancing and in standard work arrangements in Malaysia view a trade-off between flexibility and income and are willing to forgo a share of earnings for greater flexibility. We deploy a novel discrete choice experiment in which respondents are asked to choose their preferred job from two hypothetical job descriptions with randomly assigned attributes viz. flexibility, and associated earnings. We find substantial but not overwhelming preference for greater flexibility, especially among freelancers, and a clear trade-off between measures of flexibility and income. We also find considerable variation in the preference for flexibility, much of which is not explained by worker demographics and other observable characteristics but is consistent with other measures of the importance attached to flexibility and earning income. Our analysis outlines pathways through which offering even a modicum of flexibility can enhance workers' utility without necessarily increasing costs for employers and provide evidence of considerable preference heterogeneity and warns against imposing uniform approaches to (in)flexible work arrangements.
Keywords: J30; J32; M52; 330; flexibility; flexible work arrangements; gig work